Identifikasi Hambatan dan Solusi dalam Implementasi Merdeka Belajar Kampus Merdeka di Perguruan Tinggi Swasta - Tobondo, Yuyun Alfasius; Tondowala, Sulvia Fery Hanry (Interdisciplinary Journal (IDe), 2023)
This study aims to identify the obstacles and solutions in the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy in private universities in Indonesia. The method used is the Systematic Literature Review (SLR), which allows for a deep and holistic understanding of social phenomena. Researchers collected literature sources from databases such as PubMed, Scopus, Google Scholar, and IEEE Xplore with keywords relevant to the research topic. The results of the study indicate that the main challenges in implementing MBKM include issues of governance, management, and limited budget allocation. Other obstacles include a lack of human resources, limited collaboration with industry, and the emergence of new corrupt practices. To overcome these challenges, it is crucial to improve coordination between the central government and local schools and to provide adequate facilities and infrastructure. Effective implementation of the MBKM curriculum can enhance communication skills, critical thinking, creativity, and collaboration among students, preparing them for the ever-evolving workforce. This study concludes that strengthening policies and practices supporting independent education can improve the quality of higher education in Indonesia and provide significant benefits to students and related educational institutions.